Pendampingan Belajar Siswa Pada Masa Pandemi Di Dusun Terek Karanganyar - Cendi Maya; Fatimah Cahyaningrum; Nurhana Pratiwi; Nur Asiyah; Putri Astuti; Sari Kurniati; Suhendro (Jurnal Pengabdian kepada Masyarakat Radisi, 2021)
The Covid-19 pandemic has changed the pattern of community activities, including in teaching and learning activities (KBM). Teaching and learning activities that were initially carried out face-to-face, with current conditions, are required to study remotely according to the regulations of the Ministry of Education and Culture. Elementary school students will be in dire need of learning assistance. The implementation of distance learning activities encountered several obstacles. The development of students' learning motivation showed positive results accompanied by the enthusiastic attitude of students in participating in tutoring activities. The development of student achievement on average shows a positive development towards a better direction.